Industrial Aviation Management A Primer in European Design, Production and Maintenance Organisations - Hinsch, Martin (Springer Berlin Heidelberg : Imprint: Springer, 2019)
This book outlines the structure and activities of companies in the European aviation industry. The focus is on the design, production and maintenance of the components, assemblies, engines and the aircraft itself. In contrast to other industries, the technical aviation industry is subject to many specifics, since its activities are highly regulated by the European Aviation Safety Agency (EASA), the National Aviation Safety Authorities and by the aviation industry standard EN 9100. These regulations can influence the companies' organization, personnel qualification, quality management systems, as well as the provision of products and services. This book gives the reader a deeper, up-to-date insight into today's quality and safety requirements for the modern aviation industry. Aviation-specific interfaces and procedures are looked at from both the aviation legislation standpoint as well as from a practical operational perspective. Dr. Martin Hinsch has over 15 years of aviation industry experience. He worked for Lufthansa Technik in Germany, Switzerland and the Middle East, focusing on Process & Quality Management. He holds a Professorship in Aviation Management, is a certified aerospace auditor according to EN 9100, and he is also the CEO of AeroImpulse - Aerospace Consulting. Dr. Hinsch has authored several books on aviation management to critical acclaim.